Geosmithia Species Associated With Bark Beetles From China, With the Description of Nine New Species - Zhang, Xiuyu; Li, You; Si, Hongli; Zhao, Guoyan; Kolařík, Miroslav; Hulcr, Jiri; Jiang, Xiaoqian; Dai, Meixue; Chang, Runlei (Frontiers in Microbiology, 2022)
Fungi of the genus Geosmithia are frequently associated with bark beetles that feed on phloem on various woody hosts. Most studies on Geosmithia were carried out in North and South America and Europe, with only two species were reported from Taiwan, China. The aim of this study was to investigate the diversity of Geosmithia species in China. Field surveys in Fujian, Guangdong, Guangxi, Hunan, Jiangsu, Jiangxi, Shandong, Shanghai, and Yunnan yielded a total of 178 Geosmithia isolates from 12 beetle species. Isolates were grouped based on morphology. The ITS, β-tubulin and elongation factor 1-α gene regions of representatives of each group were sequenced. Phylogenetic trees were constructed based on those sequences. In total fourteen species were identified, with three previously described species G. xerotolerans, G. putterillii, and G. pallida, and eleven new species which were described as G. luteobrunnea, G. radiata, G. formosana, G. brevistipitata, G. bombycina, G. granulata (Geosmithia sp. 20), G. subfulva, G. pulverea (Geosmithia sp. 3 and Geosmithia sp. 23), G. cucumellae, G. fusca, and G. pumila sp. nov., in this paper. The dominant species obtained in this study were G. luteobrunnea and G. pulverea.